Population Status of Baya Weaver (Ploceus Philippinus) in Peninsular Region Saurashtra of Gujarat, India - Pathan, Yusufkhan; Goswami, Arvindgiri; Trivedi, Varsha M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The Baya Weaver (Ploceus philippinus) is a weaver bird found across the Indian Subcontinent and Southeast Asia. The study was concerned with the population status of Baya weavers among the peninsular region Saurashtra of Gujarat, India. Fieldwork was conducted over six months across 17 sites in Rajkot City, utilizing focal and point count methods for bird population assessment. Observations recorded the spatial and temporal distribution of P. philippinus populations. Statistical analyses (Two-way ANOVA) revealed significant spatial (P=0.0013) and temporal (P=0.0201) variations in population dynamics. An average total population of Baya Weaver at different site records 55.25 individuals, average male population was higher (30.41) than female population (24.82). The spatial distribution confirmed that the Baya Weaver population was greater near rural and suburban areas while decrease in urban areas. As the breeding season of this bird is between April to October, temporal distribution suggested that maximum male and female population of Baya Weaver was recorded during October; whereas minimum population recorded in November. All sites of the study reflected a higher male population than a female population. The population of P. Philippinus tends to decline due to diet and habitat loss because of rapid urbanization as well as industrialization. This study underscores the importance of continuous monitoring and conservation efforts for P. philippinus, emphasizing the need for research on breeding ecology, habitat preferences, and the impacts of agricultural practices to develop effective conservation strategies.